Association of −344C/T polymorphism in the aldosterone synthase (CYP11B2) gene with cardiac and cerebrovascular events in Chinese patients with hypertension. Issue 9 (September 2020) - Wang, Lili; Zhang, Zhi; Liu, Dongxia; Yuan, Kexin; Zhu, Guohua; Qi, Xiaoyong
Objective: Several recent studies have shown that the aldosterone synthase gene ( CYP11B2 ) −344C/T polymorphism is related to cardiovascular diseases. However, whether the −344C allele influences the incidence of cardiovascular diseases in Chinese patients with hypertension is unclear. Methods: Chinese patients with essential hypertension were genotyped for the −344C/T polymorphism in CYP11B2 (n = 755; CC, n = 112; CT, n = 361; TT, n = 282) and followed for 11 years for major adverse cardiovascular events (MACEs), including stroke, onset of coronary artery disease (CAD), and CAD-related death. Established cardiovascular risk factors were used to adjust the multivariate Cox analysis. Results: After a mean follow-up period of 7.60 ± 1.12 years, a significantly higher incidence of MACEs was seen in patients with the CC genotype than in those with the CT and TT genotypes. The CC variant was significantly and independently predictive of MACEs (hazard ratio = 2.049), CAD (hazard ratio = 1.754), and stroke (hazard ratio = 2.588), but not CAD-related stroke or death. Conclusion: The CYP11B2 −344 CC genotype is a risk factor for CAD and stroke, independent of other established cardiovascular risk factors in Chinese patients with hypertension.